Education, globalization and literacy in Iberoamerica - Gómez Gallardo, Luz Marina (2014)
This article aims to analyze the austere new educational reality conditioned by globalizing phenomena of our time. It also shows the process of literacy in the Latin American region since long forgotten, and through the Peruvian case as an example, it tries to insert the most vulnerable people in society in the Latin current globalization process.